implementation of independent curricullum in cultural arts subject - Noviyanti, Shobihatul Fitroh; Galeh, Cyndika; Latifah, Rochimatul; Erningtyas, Firna; Amelia, Isnaini Infiq Nur (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study examines the use of teaching modules, implementation of learning, and obstacles faced in implementing the Independent Curriculum in the subject of Arts and Culture at the Nahdlatul Ulama Polowijen Private Elementary School. The study was conducted using a descriptive qualitative approach through observation and interviews. The results of this study resulted in the Teaching Module being used as the main guideline in planning learning that is adjusted to the potential and development phase of students. The implementation of learning applies a reciprocal and exploratory model, which provides space for students to actively create and collaborate, especially in drama projects. The learning process is fun, interactive, and fosters self-confidence and cultural appreciation. The main obstacles found were limited facilities and infrastructure such as musical instruments and art materials, as well as unequal access to technology. However, the school took the initiative to overcome obstacles through the use of local materials and teacher creativity.